Cronbach’s Alpha and Semantic Overlap Between Items: A Proposed Correction and Tests of Significance - Alkhadim, Ghadah S. (Frontiers in Psychology, 2022)
The purpose of the present study was to address the shortcomings of Cronbach’s alpha concerning the semantic overlap between items. Using an example from a motivational measure, the correction of Cronbach’s alpha was applied by partialing out the effects due to conceptual overlap. The significance of Cronbach’s alpha was tested using simulated random data derived from the measure and by estimating the confidence intervals with known and unknown distributions. The results indicated that the uncorrected conceptual overlap coefficient alpha was equal to 0.89 and 0.66 following the correction. After simulating the corrected statistical results, the distribution of alpha with random numbers had an estimate of 95%, equal to 0.41. The lower bound of the corrected alpha distribution was equal to 0.41, suggesting that the corrected alpha could easily belong to the distribution of alpha developed from simulated random numbers. Thus, the semantic overlap between items on a measure represents a significant threat to the validity of the alpha coefficient.